A case of fungal keratitis caused by Scopulariopsis brevicaulis: treatment with antifungal agents and penetrating keratoplasty. Issue 9 (September 1990) - Ragge, N K; Hart, J C; Easty, D L; Tyers, A G
Abstract : A case of fungal keratitis caused by Scopulariopsis brevicaulis following a penetrating eye injury is described. Treatment with antifungal agents and keratoplasty resulted in a favourable outcome.